Multicultural challenges and sustainable democracy in Europe and East Asia - Kim, Nam-guk (Palgrave Macmillan, 2014)
"This collection compares the current stage of multicultural challenges and their influence on democracy in twelve countries of Europe and East Asia. While East Asia has recently experienced sociocultural cleavages and their challenges to democracy, Europe has faced increasing discontent over multiculturalism and has tried to seek alternative routes of social integration to sustain democracy. In other words, both continents have now faced the common problem of how to solve sociocultural cleavages and how to sustain democracy through overcoming multicultural challenges. Contributors examine twelve individual cases in the two continents and compare the divergence and convergence of multicultural practices, exploring different ways of achieving the shared values of democracy in a multicultural diversity. This book ultimately clarifies the differences between Europe and East Asia in their approaches to universalizing locality and localizing global norms regarding human rights and democratic individuality in the context of multicultural challenges"--